Four weeks` corticosteroid inhalation does not augment maximal power output in endurance athletes - Kuipers, H.; van`t Hullenaar, G. A. C.; Pluim, B. M.; Overbeek, S. E.; de Hon, O.; van Breda, E. J.; van Loon, L. C. (British Journal of Sports Medicine, 2008)
Objective: To assess possible ergogenic properties of corticosteroid administration. Design: A balanced, double-blind, placebo-controlled design was used. Participants: 28 well-trained cyclists and rowers. Intervention: 4 weeks` daily inhalation of 800 µg budesonide or placebo. Main outcome measurements: The subjects performed three incremental cycle ergometer tests until exhaustion, before and after 2 and 4 weeks of placebo or budesonide administration, to measure maximal power output (Wmax). Once a week they filled in a profile of mood state (POMS) questionnaire. Results: There was no significant difference in Wmax between the placebo (376 (SD 25) W) and the corticosteroid group (375 (36) W) during the preintervention test, and there were no significant changes in either group after 2 and 4 weeks of intervention. No effect of the intervention on mood state was found. Conclusion: 4 weeks of corticosteroid or placebo inhalation in healthy, well-trained athletes did not affect maximal power output or mood state. Hence no ergogenic properties of 4 weeks` corticosteroid administration could be demonstrated, which corroborates previous studies of short-term corticosteroid administration.